2016
DOI: 10.1371/journal.pone.0155584
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Atmospheric-Pressure Air Microplasmas with Amino Acids as Fundamental Processes in Aqueous Solution

Abstract: Plasma medicine is a relatively new field that investigates potential applications of cold atmospheric-pressure plasmas in bioengineering, such as for bacterial inactivation and degradation of organic molecules in water. In order to enunciate mechanisms of bacterial inactivation at molecular or atomic levels, we investigated the interaction of atmospheric-pressure air microplasmas with amino acids in aqueous solution by using high-resolution mass spectrometry (HRMS). Results show that the oxidation effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 46 publications
(45 reference statements)
3
80
0
Order By: Relevance
“…The low efficiency, the requirement of pure gases, and the limited volume of liquid that can be treated make plasma-treated water (PTW) expensive and its use in medicine and agriculture impossible. The most promising method for effective and low-cost production of PTW is treating liquids with high-density plasma generated by using air as a process gas [3,18,[23][24][25][26]. Furthermore, it may be possible to scale up production and reduce the cost of PTW by applying plasmas generated in ambient air to treat a continuous flow of liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The low efficiency, the requirement of pure gases, and the limited volume of liquid that can be treated make plasma-treated water (PTW) expensive and its use in medicine and agriculture impossible. The most promising method for effective and low-cost production of PTW is treating liquids with high-density plasma generated by using air as a process gas [3,18,[23][24][25][26]. Furthermore, it may be possible to scale up production and reduce the cost of PTW by applying plasmas generated in ambient air to treat a continuous flow of liquid.…”
Section: Introductionmentioning
confidence: 99%
“…2   739. Briefly, the plasma device consists of 29 microplasma jet units housed in a glass cup (inner diameter: 50 mm).…”
Section: Methodsmentioning
confidence: 99%
“…The most likely modification is different forms of oxidations. It has been shown that the relative reactivity of amino acids exposed to plasma treatment follows the order Met > Cys > Trp > Phe > Tyr > His [37]. The high-sequence coverage and redundancy obtained by pepsin digestion as applied in HDX-MS provides a suitable technique for investigation of oxidative modifications introduced by CAP treatment of the streptococcal virulence factor M1.…”
Section: Cap Induces Oxidation Of M1 Proteinmentioning
confidence: 99%